PENGARUH INSENTIF TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS KELAUTAN DAN PERIKANAN KABUPATEN KUTAI TIMUR - Budi Harsono (ADMINISTRASI PUBLIK, 2018)
This study is intended to determine the effect of incentives on employee morale in the Department of Marine and Fisheries of East Kutai Regency, therefore the researchers to formulate hypotheses